Membangun Karakter Moderat Dan Toleran Melalui Edukasi Anti Bulliying Di Sekolah Dasar Desa Ngetrep, Kecamatan Mojo, Kabupaten Kediri - Nisakh, Sinta Nadhiatun; Nurlailiah, Indria; Saputra, Mochammad Agung Valintino (Aktualisasi Pengabdian Masyarakat, 2025)
This study examines the importance of anti-bullying education as an instrument for developing moderate and tolerant character in elementary school children in Ngetrep Village, Mojo District, Kediri Regency. The study employed a qualitative descriptive method involving students, teachers, and the community as subjects. Data were collected through observation, interviews, and documentation of community service activities. The results indicate that bullying in elementary schools can have serious impacts on students' psychological and social development, as well as academic achievement if not addressed appropriately. Through anti-bullying education, children gain an understanding of the forms and impacts of bullying, while also being trained to cultivate empathy, mutual respect, and acceptance of differences. This program has been proven to increase students' awareness of rejecting bullying behavior and encourage the creation of a safe, inclusive, and conducive learning environment. Thus, character education based on moderation and tolerance is a long-term investment in developing a humanistic, democratic, and just generation.